2006
DOI: 10.5194/nhess-6-109-2006
|View full text |Cite
|
Sign up to set email alerts
|

Surface latent heat flux and nighttime LF anomalies prior to the M<sub>w</sub>=8.3 Tokachi-Oki earthquake

Abstract: Abstract. Surface Latent Heat Flux (SLHF) is an atmospheric parameter proportional to the evaporation from the Earth's surface. SLHF has been found to exhibit an anomalous behavior in the epicentral region prior to several coastal earthquakes. Sub-ionospheric low frequency (LF) radio sounding measurements have shown its potentiality for the short-term earthquake forecasting since the last decade. The anomalous SLHF and nighttime LF sub-ionospheric signals are found to show complementary nature associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Dey and Singh [49] found significant Surface Latent Heat Flux (SLHF) changes prior to the same earthquake. SLHF anomalies were also reported for the Colima earthquake, M = 7.8, 21 January 2003, Mexico [50] and the Tokachi-Oki earthquake, M = 8.3, 25 September 2003, Japan [51]. Reanalysis of climatic data are also involved in thermal data processing in seismic processes [52].…”
Section: Earth Surfacementioning
confidence: 94%
“…Dey and Singh [49] found significant Surface Latent Heat Flux (SLHF) changes prior to the same earthquake. SLHF anomalies were also reported for the Colima earthquake, M = 7.8, 21 January 2003, Mexico [50] and the Tokachi-Oki earthquake, M = 8.3, 25 September 2003, Japan [51]. Reanalysis of climatic data are also involved in thermal data processing in seismic processes [52].…”
Section: Earth Surfacementioning
confidence: 94%
“…Our former case studies include the (1) Kobe EQ (17 January 1995) (Hayakawa et al 1996), (2) Tokachi-oki EQ (25 September 2003) (Shvets et al 2004;Cervone et al 2006), (3) Niigata-chuetsu EQ (23 October 2004) Yamauchi et al 2007), (4) the 1999 Chi-chi EQ in Taiwan (Hayakawa et al 2005) and, (5) the 2004 Sumatra EQ (Horie et al 2007a, b). The details of seismogenic effects for these EQs are summarized in our review by Hayakawa (2009c).…”
Section: Introductionmentioning
confidence: 99%
“…For this EQ, our previous analysis of subionospheric VLF/LF data (for example, from a Japanese JJY station (in Fukushima) to Moshiri, Hokkaido and to Kamchatka, Russia) has indicated that the ionosphere was disturbed about one week before the EQ (Shvets et al, 2004;Hayakawa et al, 2005). In good correspondence to this ionospheric perturbation, Cervone et al (2006) has found the anomaly in surface latent heat flux before the EQ. The period of these anomalous phenomena seems to be coincident with that obtained in the present paper.…”
Section: Summary and Discussionmentioning
confidence: 94%